2011
DOI: 10.1159/000325947
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies of Dental Erosion and Erosive Wear

Abstract: We define erosion as apartial demineralisation of enamel or dentine by intrinsic or extrinsic acidsand erosive tooth wear as the accelerated loss of dental hard tissue through the combined effect of erosion and mechanical wear (abrasion and attrition) on the tooth surface. Most experts believe that during the last decade there has been a significant increase in the prevalence and severity of erosive tooth wear, particularly in adolescents. Even when erosive wear occurs in its milder forms, this is a matter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
126
1
54

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(181 citation statements)
references
References 86 publications
0
126
1
54
Order By: Relevance
“…Erosion is primarily the result of the non-bacterial chemical attack usually involving acidic substances by intrinsic or extrinsic etiologies, which ultimately provokes the loss of dental hard tissue (2). In the beginning, it causes the softening of the surface (3) and its progression turns it more vulnerable to mechanical processes, and dental subsequent wear if not stopped (1)(2)(3)(4) In the consequence of an excessive or unusual increasing of the consumption of acidic beverages, erosive lesions have also been more evident (1,5,6). As it is a multifactorial process, the compromising level of this event depends on the balance between chemical, behavioral and biological risk factors (2,6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erosion is primarily the result of the non-bacterial chemical attack usually involving acidic substances by intrinsic or extrinsic etiologies, which ultimately provokes the loss of dental hard tissue (2). In the beginning, it causes the softening of the surface (3) and its progression turns it more vulnerable to mechanical processes, and dental subsequent wear if not stopped (1)(2)(3)(4) In the consequence of an excessive or unusual increasing of the consumption of acidic beverages, erosive lesions have also been more evident (1,5,6). As it is a multifactorial process, the compromising level of this event depends on the balance between chemical, behavioral and biological risk factors (2,6).…”
Section: Introductionmentioning
confidence: 99%
“…Also, when eroded lesions present significant dental compromising, restorations of composite resin are commonly performed (9). With respect of this scenario, there is a lack of information if these alterations would be actually of concern in composition and structure of enamel in terms of erosive effects on interventions upon it (2,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control of dental biofilm involves different mechanisms, such as the use of dental floss, toothbrushing and use of oral mouthwashes, among others 23 . All the adolescents reported that they brushed their teeth at least once a day, and half of the sample mentioned the use of dental floss.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of the last decade there has been a significant increase in the prevalence and severity of erosive dental wear, particularly in children and adolescents 9,14,27 . In modern society dental erosion is known to be an important cause of loss of dental structure 9,14,23 .…”
Section: Discussionmentioning
confidence: 99%